Пословицы .Поговорки - Кузьмина М. (Развивающие книжки для малышей, 2018)
Экземпляры: Ф-22 (20191120) / Инвентарный номер: 94701 / Цена: / Сис.шифр: 82.3(2=411.2)-6 / Авт.знак: П 62 / ББК: 82.3(2=411.2)-6